La gestión del talento humano: estructura y desarrollo (2020)
In the present monograph carried out as undergraduate work to obtain the title of specialist in human talent management, an investigation was carried out of the different authors of human talent management, where each of them shows their point of view of the management of this fundamental area within organizations and how their structure and development has made inroads within them. Also the evolution throughout history and how much has been published in Colombia and the world on this subject. In addition, the importance of workers within companies and how they carry out their recruitment, selection, hiring, induction, training, training, promotion, compensation, evaluation, motivation, well-being, job management and health of their employees are shown, and the way in which they are located according to their professional profile so that in this way they exploit their competences and skills, and in turn be more efficient in their laboratories and responsibilities, where the benefit and success are mutual.